Gallic acid induces T-helper-1-like Treg cells and strengthens immune checkpoint blockade efficacy - Deng, B; Yang, B; Chen, J; Wang, S; Zhang, W; Guo, Y; Han, Y; Li, H; Dang, Y; Yuan, Y; Dai, X; Zang, Y; et al. (BMJ Publishing Group, 2022)
Background Foxp3+ regulatory T (Treg) cells facilitate tumor immune evasion by forming a suppressive tumor microenvironment. Therefore, immune therapies promoting Treg fragility may greatly enhance immune checkpoint blockade (ICB) efficacy in cancers.